2014
DOI: 10.1890/14-0157.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatially nonrandom tree mortality and ingrowth maintain equilibrium pattern in an old‐growthPseudotsuga–Tsugaforest

Abstract: Abstract. Mortality processes in old-growth forests are generally assumed to be driven by gap-scale disturbance, with only a limited role ascribed to density-dependent mortality, but these assumptions are rarely tested with data sets incorporating repeated measurements. Using a 12-ha spatially explicit plot censused 13 years apart in an approximately 500-year-old Pseudotsuga-Tsuga forest, we demonstrate significant density-dependent mortality and spatially aggregated tree recruitment. However, the combined eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 36 publications
9
100
0
Order By: Relevance
“…S8). The significant correlation between mortality rate and competition found in our study is in accord with those from other long-term inventory-based mortality studies in temperate forests (8,20,22) and boreal forests (12,23), but is discordant with recent studies that argued competition was not correlated with changes in mortality rate in temperate forests (6) and boreal forests (11). In these later studies, the increased mortality was attributed to the effect of drought.…”
Section: Significancesupporting
confidence: 88%
See 1 more Smart Citation
“…S8). The significant correlation between mortality rate and competition found in our study is in accord with those from other long-term inventory-based mortality studies in temperate forests (8,20,22) and boreal forests (12,23), but is discordant with recent studies that argued competition was not correlated with changes in mortality rate in temperate forests (6) and boreal forests (11). In these later studies, the increased mortality was attributed to the effect of drought.…”
Section: Significancesupporting
confidence: 88%
“…These services, however, are at risk for decline as evidence has increasingly shown that forests in many parts of the world are undergoing rapid changes (1)(2)(3)(4). Climate at the regional or global scale is often presumed to be responsible for these changes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), with surprisingly little attention being paid to the possible effects of endogenous processes despite the fact that competition is often an important force driving stand dynamics and succession (15)(16)(17)(18). How climate change and competition interplay to affect the long-term change of demographic rates and what are their relative contributions to the change are unanswered questions (19,20).…”
mentioning
confidence: 99%
“…Conversely, negative density effects are expected to act against aggregation through increased mortality and reduced growth of close neighbors. Although density dependent effects are known to be widespread among seeds and seedlings (Harms et al 2000), recent results have found negative effects of close neighbours on survivorship and growth of mature trees (Das et al 2011, Lutz et al 2014. Competition for soil nutrients (Silva et al 2009, Cattaneo et al 2013, Primicia et al 2015 and mortality by natural enemies such as pathogens, seed predators, and herbivores (Bagchi et al 2010, Steward and Beveridge 2010, Modes et al 2012, Zandavalli and Dillenburg 2015 are some of the mechanisms underlying such negative density effects.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies and reviews have highlighted regional (van Mantgem et al 2009, Peng et al 2011, Luo and Chen 2013 and global (Allen et al 2010, Wang et al 2012) decreases in tree survival, particularly in large trees (Dolanc et al 2013, McIntyre et al 2015, and some of these studies implicate climate change. In the arid West of the United States, studies of declining tree survival focus on old-growth forests, where endogenous changes in forest structure and species composition are minimal and assumed not to influence demographic trends Stephenson 2007, van Mantgem et al 2009, but see Lutz et al 2014). While old-growth forests are particularly important because they hold great ecological and social significance, they represent only 36% of the global forest (FAO 2010) and are particularly rare in temperate regions.…”
Section: Introductionmentioning
confidence: 99%